An Action Research on Basic Competence in Science and Technology in Social Studies Course - Fatih Pala (Anadolu Üniversitesi Eğitim Fakültesi dergisi)
Social Studies course is one of the basic courses that prepare students for social life. Change and development have become important in science and technology in the present time. Social Studies course has found its place in the development and change in science and technology. Developments in science and technology are given in Social Studies course, considering the basic competences in science and technology. The aim of this research is to reveal the process of activities related to the basic competence area of social studies course regarding science and technology and to determine the views of students and teachers regarding this process. The research was designed in action research pattern which is one of the qualitative research methods. The research was conducted in the first and second semesters of 2022-2023 academic year. The participants of the research are 6th grade students and their social studies teacher. The data of the research, observation form, teacher and student diaries, student products, semi-structured interview forms were gathered via video recordings of the researcher in the process. Data analysis of the research was conducted using descriptive analysis method. In the research it was concluded that the activities conducted regarding basic competence in science and technology in social studies course entertained the students during the course, the course was better comprehended and the subjects were learned easily. In addition, it was concluded that the activities related to the basic competence in science and technology in Social Studies course improved students' ability to conduct research using scientific research process, and realized the importance of the scientific ethics concept, respect for labor and citing references. Considering the results of the research, recommendations for practitioners and researchers were made.